POTENSI HASIL DAN TANGGAPAN SEMBILAN KLON TEH (Camellia sinensis (L.) O. Kuntze) PGL TERHADAP CURAH HUJAN DI KEBUN BAGIAN PAGILARAN - , RIA ARUM YULIANA; , Prof. Dr. Ir. Didik Indradewa, Dip. Agr. St. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The researchâs aims were to determine the yield potential and response of nine PGL tea (Camellia sinensis (L.) O. Kuntze) clones to rainfall variations and to choose the good ones as expectation clones which have high yield potential and resistance of rainfall variation as well. The research was conducted in February â June 2012 in block Sanderan II of Pagilaran production unit, Batang, Central Java. Tests were conducted on nine PGL tea clones, i.e. PGL 4, PGL 6, PGL 7, PGL 9, PGL 10, PGL 11, PGL 12, PGL 15, PGL 16, and TRI 2025 as comparison. The field experiment was arranged in a Completely Randomized Design (CRD) with 30 bushes of each PGL clones as replicates. The selected bushes were healthy bushes with approximately 1 m2 canopy broad. Data of yield components from 10 times plucking were collected and analyzed by variance analysis and DMRT at ï¡ = 5%. Resistance of rainfall variations is known from regress curve between monthly rainfall and monthly fresh shoots within two years period which is the secondary data. The results showed that among nine PGL clones, there were three PGL clones that were fit to be expectation clone, i.e. PGL 6, PGL 10, and PGL 16, with the yield potential of each 3,435 tons/ha/year, 3,795 tons/ha/year, and 4,115 tons/ha/year respectively. PGL 6 and PGL 10 had yield potential equal to TRI 2025, and the yield potential of PGL 16 was higher than TRI 2025. PGL 16 had the best shoot quality and shoot growth, as peko and banjhi ratio was over 1. PGL 6, PGL 10, and PGL 16 had a high resistance of rainfall variation which the shoot growth remained stable with small decreases in both low as well as high rainfall.